Popularização do transporte individual: ilusões perdidas com os automóveis e motocicletas em São Paulo - Ricardo Barbosa da Silva (Confins)
The popularization of private transport is a process that expands intensively in most Brazilian cities. In the metropolis of São Paulo, the popularization of individual transport intensifies the effect of the 1990s, with the advent of the popular car and motorcycle for popular classes. This process is the result of a speech that pointed to the market as a solution to the individual solve your problem of disabled buying a private transport. This article aims to understand the basics of this process of popularization of individual transport, as well as understand the reasons for the purchase and perception of the people who use these individual transports. Therefore, this article is based on a multi-strategy methodology, which aims to integrate the quantitative approaches, referring to statistical data that demonstrate the process of popularization of individual transport, as well as, qualitative, based on interviews emphasizing the perceptions of users of automobiles and motorcycles in their daily shifts in the metropolis of São Paulo.